2002
DOI: 10.1074/jbc.m201163200
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcal Scl1 and Scl2 Proteins Form Collagen-like Triple Helices

Abstract: The collagens are a family of animal proteins containing segments of repeated Gly-Xaa-Yaa (GXY) motifs that form a characteristic triple-helical structure. Genes encoding proteins with repeated GXY motifs have also been reported in bacteria and phages; however, it is unclear whether these prokaryotic proteins can form a collagen-like triple-helical structure. Here we used two recently identified streptococcal proteins, Scl1 and Scl2, containing extended GXY sequence repeats as model proteins. First we observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
280
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(291 citation statements)
references
References 50 publications
(44 reference statements)
10
280
1
Order By: Relevance
“…However, the observation that the recombinant CL domain of Scl1 is expressed as a stable triple helix (16,23) contrasts with this hypothesis at least in vivo. Scls have characteristic "lollipop-shaped" domain organization, which seems apt for ligand binding.…”
contrasting
confidence: 39%
See 2 more Smart Citations
“…However, the observation that the recombinant CL domain of Scl1 is expressed as a stable triple helix (16,23) contrasts with this hypothesis at least in vivo. Scls have characteristic "lollipop-shaped" domain organization, which seems apt for ligand binding.…”
contrasting
confidence: 39%
“…Scls have characteristic "lollipop-shaped" domain organization, which seems apt for ligand binding. Indeed, antibody mapping and electron microscopy imaging analyses confirmed that the stalk-forming CL region projects the globular V region away from the bacterial surface (16), a feature that may facilitate interactions of V regions with their potential targets. Several biologically relevant V region ligands have been identified using experimental approaches.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…collagen-like protein in S. pyogenes (Scl2.28) contains an N-terminal trimerization domain (V domain) followed by a CL domain with 79 Gly-Xaa-Yaa triplets (22,26,27). A construct in which the collagen domain was duplicated, VCLCL, was cloned and has been used in this study as the host for human collagen sequence insertions that may mediate binding to Fn.…”
Section: Design and Expression Of Chimeric Bacterial Collagens-amentioning
confidence: 99%
“…Here, a recombinant bacterial collagen-like protein system is employed to characterize the amino acid sequences in native and denatured collagen required for Fn binding. A collagen-like protein found in Streptococcus pyogenes, which is readily expressed and easily modified in Escherichia coli, was previously shown to have a triple helix structure and stability similar to that of human fibrillar collagens, even though post-translationally formed hydroxyproline (Hyp) is absent (22)(23)(24). Chimeric collagen-like proteins were generated by inserting potential Fn binding sequences from human collagen type II between bacterial collagen modules.…”
mentioning
confidence: 99%